Effects of high pressure and ohmic heating on shell loosening, thermal and structural properties of shrimp (Pandalus borealis). (January 2020) - Dang, Tem Thi; Feyissa, Aberham Hailu; Gringer, Nina; Jessen, Flemming; Olsen, Karsten; Bøknæs, Niels; Orlien, Vibeke
Abstract: This study aimed at understanding the effects of high pressure (HP) and ohmic heating (OH) on the peelability, the underlying mechanisms of HP- and OH-induced shell tightening, the thermal and structural properties of shrimp parts. HP improved the peelability of shrimp at low pressure level (<350 MPa) and short holding time (≤3 min) and the optimum condition for peeling was at 100 MPa for 3 min at 5 °C. However, a higher pressure level (>350 MPa) led to a decrease in the peelability. High pressure at 600 MPa stabilized cuticular and epidermal collagen and formed new collagen-like structures by new linkages, which strengthened the muscle-shell connection and reduced the peelability. Shrimp meat induced from HP at 100 MPa and 600 MPa had minorly denatured myofibrillar proteins. OH as a blanching method did not significantly improve the peelability of shrimp at most of the studied conditions. Some extreme conditions (e.g. at 50 °C) caused a markedly low peelability due to occurrence of collagen gelatinization. The gel formation from collagen-gelatin transformation under heating added strength to adherence of shell to epidermis and muscle, as a consequence, a difficult peeling was experienced. OH also denatured proteins in shrimp meat and caused loss of astaxanthin. Industrial relevance. The industrial processing of ready-to-eat shrimp involves the on-ice or in-brine maturation process which loosens the shrimp's shell from its meat, and therefore enable the mechanical peeling. However, the traditional maturation is time consuming (up to several days), inevitably leads to reduced quality of shrimp meat. This study shows the possibility of the application of HP at mild pressure levels to promote the shell loosening at short HP processing time (≤3 min). However, at more severe HP conditions could lead to the shell tightening which was caused by HP-induced stabilization of collagen in shell and epidermis. The study also shows that ohmic heating (<5 min) might not be a significant blanching method to support the maturation since OH had minor positive effect on shell loosening at some OH conditions (e.g. 2 or 10% NaCl, 92 V, and 30 or 35 °C), but had a counter effect at most OH conditions especially at high temperature. Highlights: High pressure (HP) at <350 MPa led to shell loosening, extreme HP led to shell tightening. Mild ohmic heating (OH) led to minor shell loosening, extreme OH led to shell tightening. HP-induced shell tightening was attributed to stabilization of cuticular and epidermal collagen. OH-induced shell tightening was caused by cuticular and epidermal collagen gelatinization. HP minorly denatured shrimp protein while OH caused severe denaturation.